Gender and Climate Smart Innovations: Lessons from the field from AICCRA and FSRP - Gondwe, Therese; Huyer, Sophia; Maiga, Marianne; Bullock, Renee; Adomaa, Faustina. O; Mujawamariya, Gaudiose; Diabaté, Fatoumata; Mapedza, Everisto D. (2024)
AICCRA and FSRP are implementing projects to increase agricultural productivity in African countries amidst the challenges of extreme weather conditions caused by climate change, in a gender sensitive manner. A Joint Webinar was conducted, for implementing countries of these two programs to share experiences by presenting success stories on the outcomes of mainstreaming gender while considering intersectionality and social inclusion. This publication is a synthesis of the discussions during the webinar.